Impact of Integrated Personnel and Payroll Information System (IPPIS) on Federal Universities’ Administration in Nigeria - Niyi Jacob Ogunode; Adamu Dauda Garba (Journal of Higher Education and Academic Advancement, 2024)
This paper discussed the Impact of the Integrated Personnel and Payroll Information System (IPPIS) on the federal universities administration in Nigeria. Secondary data were employed in the paper. The secondary data were collected from print and online publications. The paper concluded that the positive impact of the Integrated Personnel and Payroll Information System (IPPIS) on the federal universities administration includes; a reduction of strikes in federal universities as a result of the management-labour union crisis over unpaid arrears, a reduction of corruption and reduction in administrative wastages. The paper also identified the negative impacts of the implementation of the Integrated Personnel and Payroll Information System (IPPIS) on the federal universities administration including termination of appointment of contract staff, shortage of academic staff, slow in federal university administration and violation of federal universities autonomy. Based on the impacts identified, the paper hereby recommended that federal universities in Nigeria should be removed from the Integrated Personnel and Payroll Information System (IPPIS) platform and be granted full autonomy to operate according to global best practice.